Preceding expansion in the treatment of dermatofibrosarcoma protuberans involving the frontal bone - Erick Horta Portugal; José Carlos Ribeiro Resende Alves; Aloísio Ferreira da Silva Filho; Rebeca Paohwa Liu da Fonseca; Nárlei Amarante Pereira; Augusto César de Melo Almeida; José de Souza Andrade Filho (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Dermatofibrosarcoma protuberans is a rare skin tumor with intermediate malignancy and low metastatic potential, but a high recurrence rate after surgical treatment. Treatment involves extended resection with variable margins. METHODS: Patients were managed with preceding expansion of tissues of the forehead using two conventional expanders. The lateral margins of normal-appearing tissue 3-cm apart were tattooed with China ink. In a preceding operation, expanders were inserted through skin incisions at a distance from the marks, by undermining the surgical plane just above the periosteum, while preserving the area of wide resection previously delimited. After the lateral tissues were expanded, the patients underwent surgical resection. The deep margin included the outer table of the frontal bone. The expansion period averaged 45 days. RESULTS: Three cases of dermatofibrosarcoma protuberans of the forehead with involvement of the outer table of the frontal bone are described. The expanded flaps easily closed the defects. The average follow-up was 194 months without tumor recurrence. CONCLUSION: Preceding expansion of forehead tissue in the treatment of dermatofibrosarcoma protuberans with invasion of frontal bone, using 3-cm lateral margins and removal of the outer table of the frontal bone, allowed easy closure of the defect in 3 different patients. Average follow-up of 194 months with no recurrence of the lesion showed the effectiveness of the method.